Do foreign mergers and acquisitions boost firm productivity? - Marc Schiffbauer; Iulia Siedschlag; Frances Ruane (The Economic and Social Research Institute (ESRI), 2009)
This paper examines the causal relationship between foreign mergers and acquisitions and firm productivity in the UK over the period 1999-2007. Our results raise questions about the existence of aggregate effects of foreign ownership on TFP in the longer-run. However, we find significant heterogeneity in the TFP effects of foreign M&A at the industry level. Overall, we uncover a systematic pattern of post-acquisition TFP effects that is consistent with the most recent theoretical models of firm heterogeneity and cross-border mergers and acquisitions as mode of foreign entry. Furthermore, we find positive aggregate effects on labor productivity due to capital deepening but not due to changes in TFP.
Keywords: F23; D24; O33; 330; cross-border mergers and acquisitions; productivity; firm heterogeneity; Multinationales Unternehmen; Direktinvestition; Übernahme; Produktivität; Großbritannien